TINJUAN YURIDIS PENGEMBANGAN SISTEM PERADILAN PIDANA DALAM RUU KUHAP - Setiady, Tri (Yustitia, 2013)
Thirty years after the Criminal Code enacted in Indonesia . Law No. 8 of 1981 on the statute books of the criminal procedure law enforcement initially seen as a " masterpiece " of Indonesia to respect human rights in general , and especially those who lodged a criminal case . However , now the Criminal Procedure Code deems unsuitable to " change the system of constitutional and legal developments in society that needs to be replaced with new penal procedural law " ( preamble " weigh c " Draft Code of Criminal Procedure ) . In general explanation of the Criminal Procedure Code bill put forward a number of indicators that show the outdated Criminal Code